2022
DOI: 10.3389/fpsyg.2022.830935
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Anxiety, Family Violence, Suicidality, and Wellbeing in Pakistan During the COVID-19 Lockdown: A Cross-Sectional Study

Abstract: Background and ObjectivesThe purpose of this study was to draw the attention toward the implications of COVID-19 and the related restrictions imposed worldwide especially in Pakistan. The primary objective was to highlight the levels of psychological distress, anxiety, family violence, suicidality, and well-being due to COVID-19 and the secondary objective was to associate it to social demographic factors.Materials and MethodsIt is designed as a cross-sectional study by employing an online questionnaire in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…A research from Pakistan also documented higher psychological distress and anxiety but low well-being among participants due to lockdown. 8 Another research indicated greater prevalence of distress among Indians during the pandemic. 9 The disease developed fear of being its victim, causing stress, helplessness, and stigma pertaining to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A research from Pakistan also documented higher psychological distress and anxiety but low well-being among participants due to lockdown. 8 Another research indicated greater prevalence of distress among Indians during the pandemic. 9 The disease developed fear of being its victim, causing stress, helplessness, and stigma pertaining to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Also Covid-19 resulted in increased cases of domestic violence and assault in western countries. 3 They also suggest that women suffer more from maxillofacial injuries as a result of domestic violence with prevalence ranging from 34-73%. 9 All the others modes of injuries 7 (3.5%) were similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 Being in direct contact with the virus health care workers suffered more from the stress than the general masses. 3,7 Various governments responded differently according to their own circumstances from partial to complete lockdowns. 1 It was advised to ensure at least the minimal protection i.e., N95 mask and an eye goggle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations